Antibacterial efficacy of Rosella (Hibiscus sabdariffa Linn) flower extract against Streptococcus sanguis - Nafisa, Durotun; Dewi, Warta; Rachmawati, Emma (Padjadjaran Journal of Dentistry, 2015)
Introduction: Rosella is well known as health drink that contains anti bacterial compounds. The purpose of this research is to examine the anti bacterial potential of rosella calyx ethanol extract towards Streptococcus sanguis. Methods: Streptococcus sanguis was obtained from students’ saliva in the clinic of the Faculty of Dentistry, Universitas Padjadjaran. It was cultured in blood agar and incubated for 18 to 24 hours at 37°C in a facultative anaerobic environment. Streptococcus sanguis was isolated based on the characteristics of the colonies formed, Gram staining, inulin and rafinose fermentation tests. The anti bacterial test was performed using agar diffusion method (Kirby Bauer Method) by making agar holes in the agar and filling them with rosella extract with concentrations at 0.20 g/ml, 0.10 g/ml, 0.05 g/ml and 0.025 g/ml. Results: The results of this research show that there was anti bacterial activity from the ethanol extract of rosella calyx with the inhibition zones of 19.85 mm, 12.05 mm, 8.45 mm and 3.65 mm under rosellas’s extract’s concentration of at 0.20 g/ml, 0.10 g/ml, 0.05 g/ml and 0.025 g/ml respectively. Conclusion: The conclusion of this research is rosella calyx ethanol extract has the greatest anti bacterial activity at concentration 0.20 g/ml.